Evaluating the food safety standards and competitiveness of South Africa's oranges in strategic Asian Markets - Phaleng, Lucius Tshwene (My University, 2024)
This study aims to measure the effect of food safety standards and competitiveness of South African orange exports destined for strategic Asian markets. The study goal is to provide policymakers with insights to assist South Africa secure a larger market share in Asia by addressing critical factors. The research focuses on ten (10) strategic Asian markets: Hong Kong, India, Indonesia, China, Thailand, Japan, Malaysia, the Philippines, Vietnam, and South Korea. The study sets out to outline the composition and trends in South Africa’s orange exports to these Asian markets; analyze the competitive performance of other countries; identify key challenges and areas for improvement within the domestic orange industry and further assess the food safety requirements in these markets. The study employed both primary and secondary data. The first objective was based on desktop analysis and the data was sourced from reputable data platforms. The findings indicated that South Africa has seen significant growth in orange exports to Asian markets, surpassing Europe in 2005 and 2006. Despite a slight decline in 2007, Asia remains a critical market for South African exports. South Africa’s competitive performance against the competing countries in Asian markets was measured using the relative comparative advantage (RCA), net export index (NXi), relative trade advantage (RTA), and constant market share (CMS) analysis. South Africa’s orange industry demonstrated a strong comparative advantage, with RCA values consistently high with 25% indices indicating robust competitiveness. Despite competition from countries like Egypt and Greece, South Africa maintains a strong position. The net export index (NXi) reported an average near 100 indicating the favourable net export performance of the South African orange industry. The main constraints and drivers of the South African orange industry were measured using a distributed survey of the exporters of oranges. A total of 102 surveys were distributed to various stakeholders in the orange industry, with 67 completed responses, yielding a response rate of 65.7%. The main challenges that discourage the local orange competitiveness include issues like the quality of unskilled labor, political trust, electricity supply, health concerns, land reform policies, BEE policies, and crime. Additionally, poor infrastructure and ineffective trade agreements exacerbate these challenges. Specifically, the poor performance of South African ports leads to higher freight costs and delays, negatively impacting product quality and profitability. Lastly, the gravity model was utilized to assess the effect of food safety standards on South African orange exports through STATA. It was revealed that an increase in importers' GDP by 1% decreases South Africa's export performance, while a rise in South Africa's GDP enhances it. Population growth in these markets positively influences export volumes. Furthermore, the exchange rate volatility at the 5% level appears to support rather than hinder export growth, suggesting resilience within the industry. The study highlights that Technical Barriers to Trade (TBT) and Sanitary and Phytosanitary (SPS) measures significantly hinder South Africa’s orange exports. These barriers are statistically significant and align with existing literature, emphasizing the need for better negotiation and policy alignment. Therefore, to enhance food safety compliance in South Africa’s orange industry, it is crucial to implement robust monitoring systems that adhere to technical barriers to trade and sanitary and phytosanitary standards. This will improve the quality of oranges and reduce shipment rejections, leading to better access to Asian markets. Developing specific trade agreements to address TBT and SPS barriers will improve market access and lower compliance costs, while ongoing analysis of market data will help the orange industry adapt to changing conditions and seize emerging opportunities. Additionally, investment in port infrastructure and modern transportation systems through public-private partnerships can lower freight costs and shipping delays, ultimately improving oranges quality and competitiveness in price-sensitive markets. Targeted training programs to improve labour quality and productivity will enhance agricultural practices and post-harvest handling, supporting South Africa’s competitiveness in Asian markets. Political and economic stability is essential for fostering a favourable business environment. Engaging with the government to address land reform, empowerment policies, and crime will build trust and attract investments in the orange industry. Financial strategies like hedging are needed to mitigate exchange rate risks and ensure stable revenues. Marketing efforts highlighting the quality and sustainability of South African oranges can enhance presence and customer loyalty. Collaboration between industry leaders and government through a dedicated task force will address infrastructural and policy challenges, leading to effective operational improvements. Continuous monitoring of economic indicators will facilitate the refinement of export strategies, ensuring resilience and competitiveness in Asian markets.
Thesis (Ph. D. (Agricultural Economics)) -- University of Limpopo, 2024
Keywords: Porter model; Orange exporters; Hausman test; Gravity model; Food safety standards; Competitiveness; Asian strategic markets; Factor demand; Regression; Significance; Phytosanitary barrier; Technical barrier; Orange industry; Food industry and trade -- Safety measures; Citrus fruits -- Marketing; Asian dollar market; Food -- Safety measures